Decomposition of Phosphorus-Containing Additives at a Charged NMC Surface through Potentiostatic Holds. Issue 4 (7th February 2019) - Tornheim, Adam; Garcia, Juan C.; Sahore, Ritu; Iddir, Hakim; Bloom, Ira; Zhang, Zhengcheng
Abstract : Multiple phosphorus-containing compounds were evaluated as electrolyte additives for their reactivity at the cathode surface using LiNi0.5 Mn0.3 Co0.2 O2 (NMC532) // Li4 Ti5 O12 (LTO) cells with both cycling and high voltage potentiostatic holds. We surveyed additives including phosphite and phosphate derivatives with either trifluoroethyl, ethyl, or trimethylsilyl groups. Phosphite additives with the same substituents showed lower Coulombic efficiency (CE) and higher oxidation current during the potentiostatic hold. Regardless of substitution group, all phosphates showed slightly higher CE than the additive-free electrolyte (baseline). However, no additive significantly decreases oxidation reactions over the course of the potentiostatic hold, indicating a non-passivated surface. Post-mortem X-ray photoelectron spectroscopy analysis of the cathodes indicates that the additive with trimethylsilyl groups produces significantly more oxygen and phosphorus on the cathode surface for both phosphites and phosphates. Atomistic simulations indicate that these additives are susceptible to electrochemical and chemical oxidation, however chemical oxidation is much more likely for the phosphite additives. The identity of ligands on the phosphorus-containing additive can dramatically affect both the decomposition current and the cathode surface after the potentiostatic hold.